2021
DOI: 10.1155/2021/9238566
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Plasma-Glycosylated Hemoglobin A1c/High-Density Lipoprotein Cholesterol Ratio and Carotid Atherosclerosis: A Retrospective Study

Abstract: Background. Diabetes mellitus (DM) and dyslipidemia are the main risk factors for atherosclerosis. Elevated glycosylated hemoglobin A1c (HbA1c) and reduced high-density lipoprotein cholesterol (HDL-C) are associated with the progression of atherosclerosis. The aim of this study is at exploring the relationship between the HbA1c/HDL-C ratio and atherosclerosis evaluated using carotid artery intima-media thickness (cIMT) and carotid artery plaque. Methods. In this retrospective study, we enrolled 1304 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Even if no significant association was not objectified in the present study, hypertension and dyslipidemia remain the main cardiovascular risk factors most associated with diabetes as in the literature 29 . Moreover, other authors had shown that these risk factors were significantly associated with carotid atherosclerosis 20,31 . Since, these are pathological conditions that aggravate the development and progression of atherosclerotic lesions 32 .…”
Section: Discussionmentioning
confidence: 48%
“…Even if no significant association was not objectified in the present study, hypertension and dyslipidemia remain the main cardiovascular risk factors most associated with diabetes as in the literature 29 . Moreover, other authors had shown that these risk factors were significantly associated with carotid atherosclerosis 20,31 . Since, these are pathological conditions that aggravate the development and progression of atherosclerotic lesions 32 .…”
Section: Discussionmentioning
confidence: 48%
“…Obesity increases systemic inflammation and leads to atherosclerosis. A high correlation between subclinical atherosclerosis and hemoglobin A1c and the duration of diabetes affects plaques and the stenosis of coronary arteries, the atherosclerosis of carotid arteries, and ABI [ 41 ]. The progression of atherosclerosis in the carotid and coronary arteries is aggravated by hyperglycemia [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older age and diabetes mellitus are known risk factors for carotid plaque formation and atherosclerosis [ 38 , 39 ]. The metabolic disorders that accompany diabetes, such as chronic hyperglycemia, dyslipidemia, and insulin resistance, lead to impaired function of vascular endothelial cells, smooth muscle cells, and platelets, which predisposes patients to carotid plaques [ 40 42 ]. Researchers have reported a higher prevalence and incidence of carotid plaques in men than in women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%